1980
DOI: 10.1002/bbpc.19800840111
|View full text |Cite
|
Sign up to set email alerts
|

The Electrooxidation of Glucose in Phosphate Buffer Solutions: Kinetics and Reaction Mechanism

Abstract: The electrochemical oxidation of glucose on Pt at pH = 7.5 within 400 2 qRHE s 800 mV was studied by cyclic voltammetry, by taking quasistationary current-potential curves, by measuring the surface coverage of organic residues, and by analyzing the primary reaction product. The results can be summarized as follows:1. Glucono lactone is the only reaction product being formed by the anodic process. Gluconic acid is generated by hydrolysis. 2. Tafel lines had to be normalized for the uncovered surface with the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 16 publications
6
78
0
Order By: Relevance
“…In both ␣-and ␤-glucose, the hydrogen atom tethered to C 1 (dehydrogenation at C 1 carbon) carbon is activated, as the acidity of the hemi-acetalic OH group is stronger than the alcoholic OH. This is well supported by the early studies on electrochemical oxidation of glucose on Pt in neutral phosphate buffer solution [20,22]. ␤-Glucose is the most reactive species among the possible anomeric forms and the geometric orientation of the hydrogen atom bound to the anomeric carbon is thought to be responsible for the poor reactivity of ␣-glucose [21].…”
Section: Introductionmentioning
confidence: 88%
“…In both ␣-and ␤-glucose, the hydrogen atom tethered to C 1 (dehydrogenation at C 1 carbon) carbon is activated, as the acidity of the hemi-acetalic OH group is stronger than the alcoholic OH. This is well supported by the early studies on electrochemical oxidation of glucose on Pt in neutral phosphate buffer solution [20,22]. ␤-Glucose is the most reactive species among the possible anomeric forms and the geometric orientation of the hydrogen atom bound to the anomeric carbon is thought to be responsible for the poor reactivity of ␣-glucose [21].…”
Section: Introductionmentioning
confidence: 88%
“…3, red curve). Peak "a" (-0.7 V) was attributed by many authors to dehydrogenation of anomeric carbon under adsorption control [23][24][25]. The dehydrogenation of the anomeric carbon peak was deeply investigated by Beden et al on a platinum electrode [26,27].…”
Section: Glucose Oxidation By Gold Nanoparticles Onmentioning
confidence: 99%
“…At the anode, glucose is predominantly oxidized to glucono-lactone, releasing two electrons and two protons. Gluconolactone undergoes hydrolysis to form gluconic acid [14]. A number of studies showed that gluconic acid can be further oxidized, but at comparably slower reaction rates [15][16][17][18][19].…”
Section: Electrode Reactions and Theoretical Potentialsmentioning
confidence: 99%